A Bacterial Consortium and Synthetic Fertilizer Based Biocontrol Approach Against Potato Rot Disease “Neocosmospora rubicola” - Riaz, Muhammad; Mahmood, Rashid; Antar, Mohammed; Akhtar, Naureen; Khan, Salik Nawaz; Anjum, Muhammad Ashfaq; Smith, Donald L. (Frontiers in Agronomy, 2022)
The study was designed to evaluate the potential of three strains of Plant Growth Promoting Bacteria (PGPB) to manage the disease caused by Neocosmospora rubicola, a rot-causing pathogen in various plant species, including potato. In the first experiment, the bacterial strains; Azotobacter chroococcum, Azospirillum lipoferum, and Pseudomonas putida and their combinations were evaluated on PDA medium against N. rubicola using the dual culture technique. All three bacterial strains were found effective in reducing the radial growth of the fungus. In the second experiment, in the presence of half and full recommended doses of N and P, the potato growing medium was inoculated with only N. rubicola and with the combination of PGPB strains. N. rubicola increased stem and tuber rot, and decreased tuber weight by 11% compared to the control. On the other hand, a sole inoculation of the biofertilizer increased tuber weight significantly. Inoculation of N. rubicola alone or in combination with the biofertilizer a week before PGPB strains application did not affect tuber weigh. However, biofertilizer inoculation a week prior to N. rubicola controlled rot symptoms and increased tuber weight by 32%. An increase in P application favoured the PGPB strains in controlling rot in tubers. The interaction effect of N with the biological treatment of biofertilizer and the pathogen was non-significant; however, the main impact of N was to increase rot in tubers and decrease in stems. It is concluded from the results that a prerequisite application of PGPB strains is an effective tool against N. rubicola infestation in potatoes.